2006
DOI: 10.1080/08035250500437507
|View full text |Cite
|
Sign up to set email alerts
|

Tap-water enema for children with myelomeningocele and neurogenic bowel dysfunction

Abstract: Transrectal irrigation with tap water is a safe method to resolve constipation and faecal incontinence in children with myelomeningocele and neurogenic bowel dysfunction, but it does not help children to independence at the toilet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 19 publications
1
58
1
Order By: Relevance
“…Relief of constipation was successfully achieved in all 40 children and faecal continence was achieved in 35; the other 5 children had faecal soiling less than once per month. 30 Overall, 90% of parents spontaneously reported general improvements in the well-being of the child, including improved appetite, increased alertness and fewer complaints of stomach pain and headache. 30 There are few data from clinical studies of TAI in adults with spina bifida.…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 97%
See 1 more Smart Citation
“…Relief of constipation was successfully achieved in all 40 children and faecal continence was achieved in 35; the other 5 children had faecal soiling less than once per month. 30 Overall, 90% of parents spontaneously reported general improvements in the well-being of the child, including improved appetite, increased alertness and fewer complaints of stomach pain and headache. 30 There are few data from clinical studies of TAI in adults with spina bifida.…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 97%
“…30 Overall, 90% of parents spontaneously reported general improvements in the well-being of the child, including improved appetite, increased alertness and fewer complaints of stomach pain and headache. 30 There are few data from clinical studies of TAI in adults with spina bifida. Of the 15 adults with spina bifida included in one observational study, 6 were prescribed retrograde colonic washout (system type not reported) as all or part of their bowel management routine: 3 of 6 patients achieved continence.…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 97%
“…6,[15][16][17][18] The follow-up of children after initiation of transanal irrigation varied widely both within and across the studies. Where detailed, follow-up and data collection occurred from 3 months, 10 4 months, 8,17 12 months, 4 33 months, 14 64 months 6 to 96 months. 8 Findings of the review This evidence-based narrative review aimed to explore how effective and acceptable transanal irrigation is within this population and the findings are discussed within these two sections.…”
Section: Details Of the Included And Excluded Studiesmentioning
confidence: 99%
“…13 Saline (either isotonic or made by families within the home) was used to irrigate the bowel in 8 of the 17 studies, 4,7,12,[15][16][17][18][19] which included 495 children. Tap water was used in 7 of the studies, 5,6,8,[9][10][11]14 which in total included 270 children. One paper did not report the type of solution used to irrigate the bowel.…”
Section: Effectiveness Of Transanal Irrigation In Childrenmentioning
confidence: 99%
See 1 more Smart Citation